2014
DOI: 10.1177/1933719113518987
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Fluid Metabolomic Analysis in Spontaneous Preterm Birth

Abstract: Objective: To identify metabolic changes associated with early spontaneous preterm birth (PTB; <34 weeks) and term births, using high-throughput metabolomics of amniotic fluid (AF) in African American population. Method: In this study, AF samples retrieved from spontaneous PTB (<34 weeks [n ¼ 25]) and normal term birth (n ¼ 25) by transvaginal amniocentesis at the time of labor prior to delivery were subjected to metabolomics analysis. Equal volumes of samples were subjected to a standard solvent extraction me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 42 publications
1
76
1
Order By: Relevance
“…The most biological specimens employed in metabolomics are serum/plasma (Kim et al, 2013), urine (Dieme et al, 2014), saliva (Santone et al, 2014), cerebrospinal fluid (Lista et al, 2014), bile (Nagana Gowda et al, 2009), seminal fluid (Kumar et al, 2014), amniotic fluid (Menon et al, 2014), synovial fluid (Giera et al, 2012), exhaled breath condensate (Leung et al, 2013), tissue extract (Wu et al, 2008), blister and cyst fluids (Hosch et al, 2008), fecal extracts (Walker et al, 2014), dialysis fluids (Qi et al, 2011), as well as tissue biopsy samples and their lipid and aqueous extract, such as from vascular tissue in studies of atherosclerosis (Martinez-Pinna et al, 2010). In the fields of autoimmune diseases, the common specimens are serum/plasma, urines, fecal extracts, and different tissue extracts or biological fluids according to different autoimmune diseases affecting different organ systems.…”
Section: Overview Of Metabolomicsmentioning
confidence: 99%
“…The most biological specimens employed in metabolomics are serum/plasma (Kim et al, 2013), urine (Dieme et al, 2014), saliva (Santone et al, 2014), cerebrospinal fluid (Lista et al, 2014), bile (Nagana Gowda et al, 2009), seminal fluid (Kumar et al, 2014), amniotic fluid (Menon et al, 2014), synovial fluid (Giera et al, 2012), exhaled breath condensate (Leung et al, 2013), tissue extract (Wu et al, 2008), blister and cyst fluids (Hosch et al, 2008), fecal extracts (Walker et al, 2014), dialysis fluids (Qi et al, 2011), as well as tissue biopsy samples and their lipid and aqueous extract, such as from vascular tissue in studies of atherosclerosis (Martinez-Pinna et al, 2010). In the fields of autoimmune diseases, the common specimens are serum/plasma, urines, fecal extracts, and different tissue extracts or biological fluids according to different autoimmune diseases affecting different organ systems.…”
Section: Overview Of Metabolomicsmentioning
confidence: 99%
“…33 Wudy et al [17] were the first to publish gas-chromatographic 34 mass spectrometric (ID/GC-MS) reference data on the concen- 35 trations of steroids in amniotic fluid (AF) of midgestation. The 36 composition of AF changes with gestational age due to the progress 37 in fetal development [18]: during embryogenesis, AF composition 38 closely resembles fetal plasma. With further development of fetal 39 membranes and the placental barrier, free diffusion of AF occurs 40 between the fetus and the AF across the skin from 10-20 weeks of 41 gestation before the onset of skin keratinization thereafter.…”
Section: Introductionmentioning
confidence: 94%
“…1). While the focus of our study was the analysis of AF steroids, 392 recent studies sufficiently used mass-spectrometric analysis to 393 uncover the AF proteom [35] and to determine AF metabolomics 394 [36]. With applications of the MS method continuously expanding, 395 future fields of AF research are evolving.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, mothers with intraamniotic infection/inflammation had a more substantial decrease in compounds of the carbohydrate cluster, and a relative increase in amino acids. Menon et al [13] collected amniotic fluid from transvaginal amniocentesis samples taken prior to delivery during active labor in an African-American population and found that the global metabolite profiles differed significantly between normal and preterm birth. Many of the significantly altered metabolites in the PTB group reflected liver metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics provides a powerful analytic tool to get insights into the complex interaction of genetics, environment and health and may serve to identify relevant predictive biomarkers for PTB. Previous work from Romero et al [12] and Menon et al [13] showed that the metabolomic profile of amniotic fluid is a good biomarker to assess the risk of preterm delivery. However, amniotic fluid sample collection is an invasive procedure with potential risk for adverse outcomes for both mother and child [14,15].…”
Section: Introductionmentioning
confidence: 99%